Does health seeking behaviour influences on quality of life of type II diabetes patients, an untouched area in diabetes, study done in JSS Hospital, Mysore - B. B., Savitha Rani; Kulkarni, Praveen; N. C., Ashok; M., Renuka; K. S., Vinay (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes mellitus is a multisystem disorder associated with number of complications. If patients are to contribute to the effective control of diabetes, awareness and practices can assist in reducing the incidence of its complications. Methods: A cross-sectional study of 200 type II diabetic patients at JSS Hospital, Mysuru was conducted, assessment of health seeking behaviour using semi structured questionnaire was done. Quality of life was assessed using WHO QOL-BREF Questionnaire. Results: Among 200 study participants 53.5% belongs to age group 41-60, 57.5% were males, 44.5% were having family history of diabetes, 68.5% were on oral hypoglycemic agents. 163 (81.5%) were anxious when they were diagnosed as diabetics, 123 (61.5%) were influenced by themselves to go for investigations, 68 (34%)were influenced by Doctors, 131 (65.5%) had no money as the barrier to attend hospital for check-up, 186 (93%) visit hospital once in less than 3 months, 180 (90%) of them believed oral drugs are the treatment for diabetes, 188 (94%) prefer Allopathic medicine. Association between initial response on diagnosis and interval for regular monitoring with Quality of life of diabetic patients was statically significant (p≤0.05). Conclusions: Health seeking behaviour is an important determinant of controlled glycaemic status and Quality of life of people living with diabetes.